Further experimental studies of two-body radiative Upsilon decays - Masek, G; Paar, H; Mahapatra, R; Briere, R; Chen, G; Ferguson, T; Tatishvili, G; Vogel, H; Adam, N; Alexander, J; Bebek, C; Berkelman, K; et al. (2002)
Continuing our studies of radiative Υ decays, we report on a search for Υ→γη and fj(2220) in 61.3 pb-1 of e+e- data taken with the CLEO II detector at the Cornell Electron Storage Ring. For the γη search the three decays of the η meson to π+ π- π0, π0 π0 π0, and γγ were investigated. We found no candidate events in the (3 π)0 modes and no significant excess over expected backgrounds in the γγ mode to set a limit on the branching fraction of B(Y→γη)< 2.1 × 10-5 at 90% C.L. The three charged two-body final states hh̄(h = π+, K+, p) were investigated for fj(2220) production, with one, one, and two events found, respectively. Limits at 90% C.L. of B(Υ→γfj) × B(fj→hh̄) ∼ 1.5 × 10-5 have been set for each of these modes. We compare our results to measurements of other radiative Υ decays, to measurements of radiative J/ψ decays, and to theoretical predictions.